Hubungan Indeks Massa Tubuh dengan Siklus Menstruasi Pada Wanita Pasangan Usia Subur Di Dusun Kumu Kecamatan Rambah Hilir - ., Andria (Jurnal Martenity and Neonatal, 2019)
Menstruation is a sign of a woman's reproductive period, which starts from menarche until menopause. The first day of bleeding is counted as the beginning of each menstrual cycle (day 1). The normal menstrual cycle is 24-32 days, while the abnormal menstrual cycle is less than 24 and more than 32 days. Abnormal menstrual cycles indicate disorders of the reproductive system. One of the factors that can cause disruption of the reproductive system is nutritional status. The purpose of this study was to determine the relationship of body mass index in women of fertile age couples in the hamlet of Kumu, Rambah Hilir sub-district. This research method is correlative analytic with cross sectional design. The sampling method is done by sampling saturated with a sample size of 50 people. Data collection is done by taking data directly using a questionnaire. Analysis of research data is univariate analysis and bivariate analysis with Chi Square test. The results obtained by respondents with abnormal BMI are more common in respondents with abnormal menstrual cycles 15 (65.2%). Whereas respondents with normal BMI had more normal menstrual cycles 23 (85.2%), the statistical test results were P = 0.002. The conclusion of this study shows that there is a relationship between body mass index and the menstrual cycle in women of fertile age couples in Kumu Hamlet, Rambah Hilir District.